Adenosine Inhibits the Release of Arachidonic Acid in Activated Human Peripheral Mononuclear Cells. A Proposed Model for Physiologic and Pathologic Regulation in Systemic Lupus Erythematosus - Sándor Sipka (The Scientific World Journal)
In the current work, the pathways are presented and reviewed showing how adenosine acts on the production and release of arachidonic acid (AA) in activated human monocytes by the involvement of various phospholipase A2 (PLA2) and protein kinase C (PKC) enzymes in physiological (normal) conditions and in a pathologic state in systemic lupus erythematosus (SLE). Two molecules of activated monocytes mainly determine the actual amounts of AA released: (1) interleukin-1β (IL-1β) increasing and (2) adenosine (Ado) suppressing this process. The AA production of monocytes mainly depends on two (IV and VI) types of PLA2 enzymes. PKCα phosphorylates the cytosolic, Ca2+-dependent and steroid-sensitive PLA2 (type IV), whereas PKCδ phosphorylates the Ca2+-independent PLA2 (type VI). By the suppression of IL-1β production in the activated human monocytes, adenosine can decrease the release of AA causing a diminished phosphorylation of both PKC isoenzymes. In SLE monocytes, the disease-specific decreased release of AA that we found earlier could be related to the decreased expression of PKCδ. These pathways are summarized in a proposed model.